A Secure Key Management Model for Wireless Mesh Networks - Gao, Li; Chang, Elizabeth; Parvin, Sazia; Han, Song; Dillon, Tharam (IEEE Computer Society, 2010)
As Wireless Mesh Networks (WMNs) are newly emerging wireless technologies, they are designed to have huge potential for strengthening Internet deployment and access. However, they are far from muture for large-scale deployment in some applications due to the lack of the satisfactory guarantees on security. The main challenges exposed to the security of WMNs come from the facts of the shared nature of the wireless architecture and the lack of globally trusted central authorities. A well-performed security framework for WMNs will contribute to network survivability and strongly support the network growth. A low-computational and scalable key management model for WMNs is proposed in this paper which aims to guarantee well-performed key management services and protection from potential attacks.